Brief biographical sketches of eight colombian 20 century architects (2004)
In Colombia new thematic publications and monographs in the field of architecture are now possible because of the growing relevance of the study of architectural archives as primary sources for research. The fragile state of many of these document sources was the motive behind the Proyect for Documental Rescue presented to the Universidad Nacional de Colombia. In a first phase many prívate archives were located and the Association for the Rescue of Architectural Archives was founded with the purpose of safekeeping documents for future research. Systematic work was begun in the offices and compa-nies of architects Giovanni Buscaglione. Joseph Martens, Ignacio Martínez Cárdenas. Roberto Pacbón. Otto Marmorek. Santiago de la Mora. José de Recaséns y Manuel de Vengoechea. The initial results of these actions (together with additional research in secondary sources) are these eight biographical sketches, which will become part of a future biographical dictionary of Colombian architects.